Streptomyces palmae sp. nov., isolated from oil palm (Elaeis Guineensis) rhizosphere soil - Kanaporn Sujarit (2018)
© 2016 IUMS. Actinomycete strain CMU-AB204Twas isolated from oil palm rhizosphere soil collected in Chiang Mai University (Chiang Mai, Thailand). Based on morphological and chemotaxonomic characteristics, the organism was considered to belong to the genus Streptomyces. Whole cellwall hydrolysates consisted of LL-diaminopimelic acid, glucose, ribose and galactose. The predominant menaquinones were MK-9(H4), MK-9(H6), MK-9(H2) and MK-8(H4). The fatty acid profile contained iso-C15: 0, iso-C16:0 and anteiso-C15: 0 as major components. The principal phospholipids detected were phosphatidylethanolamine, diphosphatidylglycerol and phosphatidylglycerol. The DNA G+C content of strain CMU-AB204Twas 70.9 mol%. Based on 16S rRNA gene sequence similarity, strain CMU-AB204Twas closely related to Streptomyces orinoci JCM 4546T(98.7 %), Streptomyces lilacinus NBRC 12884T(98.5 %), Streptomyces abikoensis CGMCC 4.1662T(98.5 %), Streptomyces griseocarneus JCM 4905T(98.4 %) and Streptomyces xinghaiensis JCM 16958T(98.3 %). Phylogenetic trees revealed that the new strain had a distinct taxonomic position from closely related type strains of the genus Streptomyces. Spiny to hairy spores clearly differentiated strain CMU-AB204Tfrom the five most closely related Streptomyces species, which produced smooth spores. On the basis of evidence from this polyphasic study, it is proposed that strain CMU-AB204Trepresents a novel species of the genus Streptomyces, namely Streptomyces palmae sp. nov. The type strain is CMU-AB204T(=JCM 31289T=TBRC 1999T).